Payroll Accounting System Analysis at CV Budi Karya - Ananta Sidik Akbar; Idang Nurodin; Sulaeman Sulaeman (Lembaga Riset dan Inovasi Al-Matani, 2023)
The purposes of this study are: 1) To explain the implementation of the payroll accounting system at CV Budi Karya., 2) To find out the obstacles in the payroll accounting system at CV Budi Karya. This study used a qualitative method with a descriptive approach. Data collection techniques used observations, interviews, and documentation. The data analysis techniques used were: data collection, data reduction, data presentation and conclusion or verification. The results of this study indicate that the results of this study indicate that: 1) CV. Budi Karya is currently still using a manual payroll system, so the company's payroll system is not yet in line with the existing payroll accounting system theory. 2) Human resources are an obstacle in the application or implementation of the accounting system at CV Budi Karya. This is inseparable from the employee's educational background and competencies. Then the approach used in this system includes making context diagrams, and payroll procedures